Experiences of enterprise resource planning system at a flagship university in Africa: Familiarity, barriers and way forward - Brown, B.; Mooketsi, R. (South African Journal of Higher Education, 2018)
Recent research has discussed the difficulties with implementing ERP systems, and the opportunities associated with the use of these systems in university contexts, but has not examined the experiences that internal stakeholders, particularly in African contexts puzzled by certain technology, have with these systems in the period after the systems ‘go-live’. This study explored these experiences, at one Flagship University in Botswana. Students, academic and administrative staff were surveyed about their familiarity with using the ERP system and the barriers they faced. Additional qualitative data probed into motives for ERP system use and concerns thereof. Findings revealed that the stakeholders showed high familiarity with, and usage of, the ERP modules tailored to their particular needs. The motives for use were mainly related to management efficiency and customer satisfaction, but not information accuracy. Information inaccuracy was an obstacle, along with academic and administrative staff relapse into old habits, weaknesses in the transitional change management, a detached persona of the university administration, and inadequate training/support, particularly for stakeholders who were not part of the system development. The gravest barriers were experienced these stakeholders. Importantly, the study offered insights into how the barriers and concerns held can be mitigated.